Student Anxiety in Doing Floor Gymnastics Movements - Hasyim, Hasyim; Hasanuddin, M. Imran; Hasanuddin, M. Irfan (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
The purpose of this study was to find out how much anxiety students majoring in physical education had to UNM Elementary School. This research is a quantitative descriptive research using surveys as the primary data collection method. The sample population used in this study amounted to 35 people. The questionnaire was the instrument used in this research project. The overall results showed that physical education students to elementary school in floor gymnastics lectures for the 2023-2024 academic year were included in the moderate anxiety category with a percentage of 54.3%.